Porothermoelasticity of thermally shocked asphalt material under a multi-phase lag model - Elsayed M. Abd-Elaziz; Mohamed I.A. Othman (Heliyon)
This investigation represents porothermoelastic asphalt material with thermal shock due to multi-phase lag model of thermoelasticity. By applying proper boundary conditions to the normal mode approach, we were able to achieve the precise solution. The graphs provide numerical results for the physical quantities supplied in physical domain. The temperature, displacement, and stress distribution numerical results are given and graphically displayed. To explain the impacts of voids, tine, and phase-lags on the field quantities, comparisons have been done. This research is interesting because it applies the multi-phase lag model and porothermoelasticity to asphalt materials, especially when considering thermal shock. The potential to enhance the longevity, performance, and sustainability of asphalt infrastructure-roadways, bridges, and runways-makes the significance wide. This research provides a more nuanced and realistic modeling method, which is crucial for developing more resilient and effective infrastructure, by taking into account delayed thermal and mechanical reactions as well as the interaction between heat, mechanical stress, and fluid flow.